Improvement of Students' Literacies Skills in The Knowledge Aspect through Science, technology, engineering, and mathematics (STEM)-Integrated Module - Fitrianti, Alfia; Suwarma, Irma Rahma; Kaniawati, Ida (Universitas Pendidikan Indonesia (UPI), 2024)
The 21st century requires students to have abilities and competencies that are by the times. These abilities and competencies include Critical Thinking, Creativity, Communication Skills, and Collaboration. This study aims to examine the improvement of Science, technology, engineering, and mathematics (STEM) literacy in aspects of knowledge after applied learning using STEM-based modules. The research method is quasi-experimental with a pretest-posttest one group. The population of this study is class X high school students in one of the high schools in Karawang, Indonesia. The institution used a multiple-choice question of 25 questions consisting of 12 questions to measure scientific literacy, 6 questions to measure mathematical literacy, and 7 questions to measure technological engineering literacy. The increase in STEM literacy is seen from the normalization gain (n-gain) analysis. STEM literacy ability has increased by looking at the results in gain g obtained by 0.69 in the medium category. The increase in STEM literacy in the knowledge aspect of science literacy results in gain g obtained by 0.66 in the medium category, the n-gain basic mathematical literacy obtained by 0.71 in the high category, and the technology-engineering n-gain literacy obtained by 0.73 in the high category. this shows that learning by using STEM-based modules can improve STEM literacy skills in alternative energy materials.